Retrieving back plastic wastes for conversion to value added petrochemicals: opportunities, challenges and outlooks - Kumar, Manish; Bolan, Shiv; Padhye, Lokesh P.; Konarova, Muxina; Foong, Shin Ying; Lam, Su Shiung; Wagland, Stuart T.; Cao, Runzi; Li, Yang; Batalha, Nuno; Ahmed, Mohamed; Pandey, Ashok; et al. (Elsevier, 2023)
Plastic production and its unplanned management and disposal, has been shown to pollute terrestrial, aquatic, and atmospheric environments. Petroleum-derived plastics do not decompose and tend to persist in the surrounding environment for longer time. Plastics can be ingested and accumulate into the tissues of both terrestrial and aquatic animals, which can impede their growth and development. Petrochemicals are the primary feedstocks for the manufacture of plastics. The plastic wastes can be retrieved back for conversion to value added petrochemicals including aromatic char, hydrogen, synthesis gas, and bio-crude oil using various technologies including thermochemical, catalytic conversion and chemolysis. This review focusses on technologies, opportunities, challenges and outlooks of retrieving back plastic wastes for conversion to value added petrochemicals. The review also explores both the technical and management approaches for conversion of plastic wastes to petrochemicals in regard to commercial feasibility, and economic and environmental sustainability. Further, this review work provides a detailed discussion on opportunities and challenges associated with recent thermochemical and catalytic conversion technologies adopted for retrieving plastic waste to fuels and chemicals. The review also recommends prospects for future research to improve the processes and cost-efficiency of promising technologies for conversion of plastic wastes to petrochemicals. It is envisioned that this review would overcomes the knowledge gaps on conversion technologies and further contribute in emerging sustainable approaches for exploiting plastic wastes for value-added products.
Keywords: Plastic waste; Petrochemicals; Thermochemical conversion technologies; Technoeconomic analysis; Life cycle assessment